The Role of Human Resource Management in Improving the Performance of MSMEs - Razak, Marwan (Newinera Publisher, 2024)
This research aims to analyze the role of Resources Management (MSDI) in improving the performance of Micro, Small, and Medium Enterprises (UMKM) in Limboto District. MSDI, as an advanced development of Human Resources Management (HRM), adopts a more holistic and humanistic approach, focusing on employee empowerment and comprehensive development. This study uses qualitative methods, including in-depth interviews with UMKM owners and employees, along with relevant secondary data analysis, to identify key factors that influence MSDI management and UMKM performance. The findings highlight the importance of structured MSDI management in improving service quality, customer satisfaction, and operational productivity. It was found that areas such as employee training, technology integration, and employee involvement in decision-making are critical to the performance improvement of UMKM. The research also discusses the challenges faced by UMKM in Limboto, including financial constraints and the lack of training and technology adoption. The study suggests that effective MSDI management, focusing on employee development and the integration of appropriate technologies, can create a more productive and competitive environment for UMKM.